2020
DOI: 10.23914/odj.v2i0.283
|View full text |Cite
|
Sign up to set email alerts
|

Collaboratory, Coronavirus and the Colonial Countryside

Abstract: Introducing the second volume of the Offa’s Dyke Journal (ODJ), this five-part article sets the scene by reviewing: (i) key recent research augmenting last year’s Introduction (Williams and Delaney 2019); (ii) the key activities of the Offa’s Dyke Collaboratory in 2020; (iii) the political mobilisation of Offa’s Dyke in the context of the COVID-19 pandemic lockdowns; (iv) the ramifications of accelerated efforts to decolonise the British countryside on both archaeological research and heritage interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Marking the fiftieth anniversary of the Llwybr Clawdd Offa/Offa's Dyke Path, Dan Llwyelyn Hall's exceptional project and published collection Walking with Offa celebrated the borderlands landscape under the unexpected and stifling threat of the COVID-19 pandemic and its attendant lockdowns when landscapes and places were especially difficult to access and experience (Llwyelyn Hall et al 2021). For the Offa's Dyke Path and the monument itself, this challenge of access, engagement and understanding was accentuated by contrasting and fluctuating lockdown strategies adopted by the UK government for England and the devolved Welsh assembly for Wales (Williams 2020a).…”
Section: Howard Williamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marking the fiftieth anniversary of the Llwybr Clawdd Offa/Offa's Dyke Path, Dan Llwyelyn Hall's exceptional project and published collection Walking with Offa celebrated the borderlands landscape under the unexpected and stifling threat of the COVID-19 pandemic and its attendant lockdowns when landscapes and places were especially difficult to access and experience (Llwyelyn Hall et al 2021). For the Offa's Dyke Path and the monument itself, this challenge of access, engagement and understanding was accentuated by contrasting and fluctuating lockdown strategies adopted by the UK government for England and the devolved Welsh assembly for Wales (Williams 2020a).…”
Section: Howard Williamsmentioning
confidence: 99%
“…Yet, of course, the interplay between Path and monument is complicated in relation to a third crucial line and division: the historic Cymric/English borderline fixed in the early sixteenth century (Fox 1955: 290-293). Whilst these three lines do coalesce for some stretches and cohere in the popular imagination, the art project tackled their shared landscape presence and their historical contingency, as well as dimensions of their material presence and their shared intangibility and complexity (Ray 2020;Williams 2020a).…”
Section: Howard Williamsmentioning
confidence: 99%
“…The practice of making comics about archaeological sites and monuments is still very much in its infancy. It is a new field, and practitioners, commissioning clients, consultants, artists and audiences are all still finding their way, figuring out what works best and how to turn the lessons from one project and one set of circumstances into guidance on how to do the next (Swogger 2019a and2020c). While all creative practice tends to have its element of quirk, serendipity and mystery, that should not simply be boiled down to 'well, you'll just have to figure it out on your own', in determining general principles or transferrable approaches.…”
Section: Practice and Processmentioning
confidence: 99%
“…The COVID-19 which started as an epidemic soon shook the world and resulted in millions of deaths that has impacted practically every area of human life globally [13]. According to [14] the global challenges were primary effects of lockdowns, government regulations and patient deferrals, and the secondary were the economic impacts of the pandemic which have led to many countries breaking down in the provision of basic and social life needs of mankind. [15] have indicated that emerging technology and advanced information technologies have opened new doors to innovation nding and enhancement for everlasting solutions to producing effective and resolute healthcare provision in our daily lives [15].…”
Section: Introductionmentioning
confidence: 99%